(untitled) (Health and Biosciences, 2023)
The Vigilância Alimentar e Nutricional is a fundamental component of health surveillance, enabling the continuous description and prediction of trends in food and nutrition of the population and their determining factors, with the data collected being consolidated in SISVAN Web. The information generated provides a diagnosis and follow-up of the population’s food and nutrition situation, which is an essential component for the development of public policies. The present study aims to describe the nutritional status of children under 10 years of age, monitored by SISVAN in a UBS in Mariana-MG. Data were obtained from the information system of the Ministry of Health, SISVAN Web, for the years 2015-2019, being collected in 2021. With regard to follow-up, 2016 had the highest number of children registered (284) and in 2015 the smallest, with 151 children. Regarding children diagnosed with overweight, the highest prevalence was recorded in 2017 (19%), with a decrease in prevalence in subsequent years (2018: 12.7%; 2019: 11.9%). With regard to thinness, the numbers are smaller, but existing, reaching a lower prevalence in 2017 (2.9%), with a progressive increase in subsequent years (2018:5.4%; 2019:8.5%). Excess weight among the monitored children showed a higher prevalence, but thinness coexisted. SISVAN, although it still has a low population coverage, proves to be an important instrument for the health team, contributing to greater knowledge of the population assisted by the SUS, in addition to assisting in the elaboration and implementation of policies and actions aimed at the nutritional needs of each population.